Durability assessment of bio-based self-compacting sand concrete with recycled granite aggregate waste against chloride and sulphate attacks - Hadjadj Moussa; Mohamed Guendouz; Djamila Boukhelkhal (Budownictwo i Architektura)
The development of sustainable high-performance concrete with improved mechanical and durability properties while incorporating environmentally friendly components is a major concern today. This work investigates the feasibility of using granite industrial waste (GW) as a natural sand substitute by volume (10, 20, 30, and 40%) combined with seashell waste powder (SWP) as a cement substitute by weight (5, 10, and 15%) to improve the durability performance of self-compacting sand concrete (SCSC) against sulphate attack and chloride permeation. The obtained results showed the feasibility of developing eco-friendly SCSC by replacing up to 40% of sand with GW and 15% of cement with SWP, with a significant improvement in compressive strength and durability properties. However, SCSC containing 40% GW and 10% SWP showed the highest compressive strength (63 MPa), a 36.65% increase in electrical resistivity, and a 48.18% decrease in chloride-ion permeability. All SCSC mixes presented electrical resistivity greater than 20 kΩ·cm and chloride-ion passed charge below 2000 C, meeting the requirements for practical engineering applications. Furthermore, the response of the SCSC mix with GW and SWP against sulphate attack was considerably better than that of the control SCSC mix. Finally, the study results in the development of an encouraging and highly resistant concrete to extreme conditions without significant material damage, while reducing the demand for natural aggregates and conventional cement.